NURSING BEHAVIOUR AND PREVENTING COVID 19 TRANSMISSION: A CASE STUDY IN MERAUKE HOSPITAL PAPUA - Sulistiyani Sulistiyani; Lamria Situmeang; Zeth Robert Felle; Eka Sriwahyuni (Lembaga Pengembangan Kinerja Dosen, 2022)
The Merauke hospital became a reference during the COVID-19 era for people living in Southern Papua - Merauke, Mappi, and Boven Digoel regencies. Thus, hospitals must prepare the nursing care staff in terms of cognition, psychomotor, and behavior in managing COVID-19. This research reviewed the nursing care behavior in preventing COVID-19 transmission at the Regional Hospital of Merauke. This cross-sectional study approach applied a total sampling technique, resulting in 60 nurses. The researchers distributed a questionnaire to collect cognitive, psychomotor, and behavioral data. From the findings, the researchers found 31 respondents, 51%, with very excellent behavior. Of those numbers, 22 respondents or 36.7% had excellent prevention while 9 respondents, or 15% had excellent prevention. From the total of 28 respondents, 46.7% had average behavior while sixteen respondents, or 26.7% had very excellent prevention. Respondents with excellent prevention consisted of 9 respondents, 15%. Respondents with average prevention consisted of 3 respondents, 5%. Then, respondents with low behavior and average prevention consisted of a respondent, 1.7%. The Chi-square obtained a p-value of 0.002, lower than 0.05. Conclusion: From the result, the researchers found the nursing behavior and COVID-19 and COVID-19 infection at Merauke Regional Hospital. The results also suggest managerial evaluation and supervision keep and improve the preventive behavior on COVID-19 transmission.